2018
DOI: 10.1186/s12987-018-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluid outflow in the rat spinal cord: the role of perivascular and paravascular pathways

Abstract: BackgroundCerebrospinal fluid (CSF) is thought to flow into the brain via perivascular spaces around arteries, where it mixes with interstitial fluid. The precise details concerning fluid outflow remain controversial. Although fluid dynamics have been studied in the brain, little is known about spinal cord fluid inflow and outflow. Understanding the normal fluid physiology of the spinal cord may give insight into the pathogenesis of spinal cord oedema and CSF disorders such as syringomyelia. We therefore aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 52 publications
(87 reference statements)
5
36
0
Order By: Relevance
“…These diseases all lead to changes in the fluid dynamics of CSF in the subarachnoid space, thus favoring the flow of CSF from the subarachnoid space into the central canal [29,30]. Some studies have confirmed that CSF passes through the spinal cord to communicate between the subarachnoid space and central canal [13,26,[31][32][33]. In our model, CSF flow was blocked due to extradural compression.…”
Section: Discussionmentioning
confidence: 84%
“…These diseases all lead to changes in the fluid dynamics of CSF in the subarachnoid space, thus favoring the flow of CSF from the subarachnoid space into the central canal [29,30]. Some studies have confirmed that CSF passes through the spinal cord to communicate between the subarachnoid space and central canal [13,26,[31][32][33]. In our model, CSF flow was blocked due to extradural compression.…”
Section: Discussionmentioning
confidence: 84%
“…This study has provided strong evidence for a normal flow of CSF to the caudal aspect of the spine within the CC in mice. The direction of the flow of CSF within the CC is a controversial topic, as conflicting data have been published in the past (Bradbury and Lathem, 1965; Milhorat et al, 1991; Cifuentes et al, 1992; Liu et al, 2018). Our conclusion of a caudally directed flow is in close agreement with Bradbury and Lathem (1965) using rabbits and subsequent work in guinea pigs and rats (Nakayama, 1976; Cifuentes et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CSF freshly produced by the choroid plexuses has access to the spine through the central canal (CC) through an aperture on the floor of the fourth ventricle. The direction of flow of CSF in either the spinal SAS (Ishibashi, 1959; Di Chiro, 1966; Davson and Segal, 1996) or the CC (Bradbury and Lathem, 1965; Milhorat et al, 1991; Cifuentes et al, 1992; Liu et al, 2018) is controversial. Most of these studies were performed under anesthetized, immobilized conditions, which limits CSF circulation (Ma et al, 2019), or involved direct injections of tracers into the intrathecal space, which may artificially induce nonphysiological tracer distribution.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that there may be regional variations, see e.g. [ 66 , 67 ]). The idea that the basement membranes of microvessels can provide a preferential route stems from observations that when horseradish peroxidase is introduced into CSF with consequential influx along arteries the peroxidase is found to be localized in the basement membranes around microvessels.…”
Section: Perivascular Pathwaysmentioning
confidence: 99%